Radiosynthesis and Biodistribution of an I-125-labeled Resveratrol Derivative - Kim, Sung Kew; Lee, Woong San; Han, Sang Jin; Kim, Eun Jung; El-Gamal, Mohammed I.; Kim, Byoung Soo; Choi, Tae Hyun; Choi, Chang Woon; Ham, In-Hye; Oh, Chang-Hyun; Choi, Ho-Young; Cho, Jung-Hyuck (KOREAN CHEMICAL SOC, 2012)
An I-125-labeled resveratrol derivative 1 was synthesized. It was purified by reverse phase HPLC. Radiochemical purity of the product was more than 98%, and the yield was 35% (decay-corrected). Its biodistribution in tumor-bearing mice was studied. The results showed that the highest radioactivity was located in intestine and stomach. The biodistribution profile suggests that compound 1 can be effectively used as a promising imaging probe for intestine and stomach.
Keywords: RED WINE; TRANS-RESVERATROL; SMALL-INTESTINE; IN-VITRO; GRAPES; CELLS; POLYPHENOL; METABOLISM; ABSORPTION; RATS